2012
DOI: 10.1039/c2dt30140g
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(ii) complexes of constrained antiviral macrocycles

Abstract: The configurations of metallocyclams are of interest in relation to protein recognition and anti-HIV activity. We have synthesised four novel zinc(II) complexes with hexyl-Me(2)-cyclam (HMC; 3,14-dimethyl-2,6,13,17-tetraazatricyclo(16.4.0.0(7,12))docosane), 1, and naphthyl-hexyl-Me(2)-cyclam (NHMC; 2,13-bis(1-naphthylmethyl)-5,16-dimethyl-2,6,13,17-tetraazatricyclo(16.4.0.0(7,12))docosane), 2, as ligands. X-ray crystallographic data for Zn(II)-HMC diacetate, 3 show that zinc is six-coordinate in a distorted oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…Subsequently, complexes of these ligands have potential to be utilised for medical imaging and therapy, such as anti-HIV drugs [1][2][3][4], magnetic resonance imaging (MRI) contrast agents [5] and positron emission tomography (PET) theranostic compounds [6][7][8][9]. The strong affinity that these ligands have for important metal ions, such as copper(II), has seen them becoming increasingly used in the formation of sensors for either environmental analysis or cellular studies [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, complexes of these ligands have potential to be utilised for medical imaging and therapy, such as anti-HIV drugs [1][2][3][4], magnetic resonance imaging (MRI) contrast agents [5] and positron emission tomography (PET) theranostic compounds [6][7][8][9]. The strong affinity that these ligands have for important metal ions, such as copper(II), has seen them becoming increasingly used in the formation of sensors for either environmental analysis or cellular studies [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…With cytotoxic concentrations of 4100 mmol L À1 , they showed high activity and low levels of toxicity to cells [23]. In our study, we introduced two methyl or ethyl substitutions on the macrocycle for steric hindrance, which may provide interesting electronic effect as well as applications in medicine [17][18][19][20][21][22][23][24]. The anionic species also play important roles in chemistry, medicine, catalysis, molecular assembly, and in biology, yet their binding characteristics have not received much recognition [25,26].…”
Section: Introductionmentioning
confidence: 96%
“…More recently, we found that L 1 and [Zn(L 1 )(OAc) 2 ] Á 0.5H 2 O were active toward viral strains HIV-1 (IIIB) and HIV-2 (ROD). With cytotoxic concentrations of 4100 mmol L À1 , they showed high activity and low levels of toxicity to cells [23]. In our study, we introduced two methyl or ethyl substitutions on the macrocycle for steric hindrance, which may provide interesting electronic effect as well as applications in medicine [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 98%
“…1,[3][4][5] It has been well understood that the carboxylate groups of the CXCR4 coreceptor play a crucial role in recognizing cyclam moieties of AMD 3100. 6 The molecular recognition between zinc(II) macrocycles and aspartates is realized by a strong Zn O covalent bond as well as hydrogen bonds between N-H group of the macrocycle and noncoordinating oxygen atom of the carboxylate group.…”
mentioning
confidence: 99%